2022
DOI: 10.1038/s41598-021-04525-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of dispersal and colonisation in a wind-borne cereal pest, the haplodiploid wheat curl mite

Abstract: Dispersal and colonisation determine the survival and success of organisms, and influence the structure and dynamics of communities and ecosystems in space and time. Both affect the gene flow between populations, ensuring sufficient level of genetic variation and improving adaptation abilities. In haplodiploids, such as Aceria tosichella (wheat curl mite, WCM), a population may be founded even by a single unfertilised female, so there is a risk of heterozygosity loss (i.e. founder effect). It may lead to adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…The success of the water pan traps collecting the SRM revealed that the mites were dispersed by air currents. The nonvolant dispersal by wind effectively covers a large area which has been recorded among the eriophyid by Kiedrowicz et al (2017); Laska et al (2022), andGalvao et al (2012), including the SRM. However, the lack of wings and visual ability makes landing random and undirected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of the water pan traps collecting the SRM revealed that the mites were dispersed by air currents. The nonvolant dispersal by wind effectively covers a large area which has been recorded among the eriophyid by Kiedrowicz et al (2017); Laska et al (2022), andGalvao et al (2012), including the SRM. However, the lack of wings and visual ability makes landing random and undirected.…”
Section: Discussionmentioning
confidence: 99%
“…The colonisation of a new habitat takes place as follows: virgin females arrive in a new habitat and oviposit unfertilised eggs resulting in all male offspring, which then shifts the proportion of males. The male sons subsequently provide spermatophores for the mothers resulting in a higher female production (Farahi et al 2018;Laska et al 2022) and subsequently drives the sex ratio to a female bias. This reproduction strategy can explain the successful colonisation of the sugarcane field by the mites even after an ecologically catastrophic event due to the burning practices during the pre-harvest and cane harvest.…”
Section: Discussionmentioning
confidence: 99%
“…The dispersion of insect pests results from an interaction among intrinsic biological characteristics of the species, biotic (availability of resources), and abiotic conditions of their environment. Successful colonization of sites by agricultural insect pests depends on the dispersal distance capacity of the individuals, the surrounding landscape characteristics (hostility of the matrix and energy wear), the availability of resources, the presence of competitors, predators, and the climatic conditions (Tischendorf and Fahrig, 2000;Laska et al, 2022). Most insect pests locate their hosts through visual and olfactory cues.…”
Section: Abstract 1 Introductionmentioning
confidence: 99%